Ultra-high resolution δ18O of land snail shell: A potential tool to reconstruct frequency and intensity of paleoprecipitation events. (15th June 2022) - Dong, Jibao; Yan, Hong; Zong, Xiulan; Wang, Guozhen; Liu, Chengcheng; Xing, Meng; Lan, Jianghu; Wei, Gangjian; Dodson, John; An, Zhisheng
Abstract: Extreme rainfall events cause tremendous threats to people's lives and economic well-being. Given the short time span of instrumental records, reconstructing the full range of past rainfall variability using available proxies is impossible when trying to unravel the history and underlying mechanisms of extreme precipitation events. However, this work is usually limited by the temporal resolution of current paleoclimate records. Here we demonstrate that the ultra-high resolution measurements of δ 18 O of terrestrial snail shells of Cathaica fasciola (Draparnaud, 1801) can be used to reconstruct the rainfall variability on weather time scales. Broadly, the modern daily time resolution snail shell's δ 18 O profile shows a negative trend from late March to September in 2020, which resembles the variations of monitored δ 18 O and amount of precipitation. Meanwhile, six abrupt negative deviations were observed in the δ 18 O profiles and these deviations matched well with the instrumental precipitation events for the same period. The high correlation of shell's δ 18 O with rainfall amount during the six precipitation events indicates that the ultra-high resolution δ 18 O records of gastropod shells have the potential to qualitatively record local synoptic rainfall events. Our study highlights that the terrestrial gastropod shell could provide daily to weekly geochemical proxies and has the potential to be used as an ultra-high resolution archive for characterizing terrestrial paleoweather, such as extreme precipitation events.